3439 Role of the Airway Microbiome in Viral Bronchiolitis Associated Respiratory Failure. (27th March 2019) - Wasserman, Emily; Worgall, Stefan; Sharma, Anurag
Abstract : OBJECTIVES/SPECIFIC AIMS: This study aims to determine if a bronchiolitis specific microbiome exists and how it evolves through disease course. Objective 1. Determine the microbiome profile of the airway in virus induced bronchiolitis-associated respiratory failure. Objective 2. Identify changes in the airway microbiome profile through the course of virus induced bronchiolitis associated respiratory failure, and the relationship between microbiome composition and clinical respiratory status. Objective 3. Determine the impact of rhinovirus infection on the lung and stool microbiome in a murine asthma model. METHODS/STUDY POPULATION: Objectives 1 &2: We are conducting a single-center prospective case-control study of patients admitted to the Komansky - Weill Cornell Pediatric Critical Care Unit. Infants less than two years of age with a diagnosis of bronchiolitis requiring intubation and mechanical ventilation are enrolled as subjects. Infants less than two years of age intubated and requiring mechanical ventilation without primary lung pathology are enrolled as controls. To evaluate our primary objective, tracheal aspirates will be collected from both subjects and controls on the day of intubation. We will perform 16s RNA sequencing on the tracheal aspirate samples and compare the resulting microbiomes. To evaluate secondary objective, we will collect tracheal aspirates of our study population on a daily basis and map the microbiome in parallel with objective measures of respiratory status including oxygen index and successful extubation. Both subjects and controls are being enrolled as a convenience sample. Objective 3: Mice, heterozygous for the sptlc2 gene (Spltc2 +/−) demonstrate reduced de-novo sphingolipids and increased airway hyperresponsiveness with methacholine challenge. Airway hyper-responsiveness is a cardinal feature of asthma. This airway hyperresponsiveness is exacerbated in the setting of rhinovirus (Figure 1). Using 16s sequencing, we will examine the lung microbiome of Sptlc2 +/− ad Sptlc2 +/+ at 1- and 7-days following rhinovirus infection. RESULTS/ANTICIPATED RESULTS: This clinical study is currently IRB approved and enrollment is ongoing. We have enrolled 12 subjects and 5 controls. Sample analysis will begin following the 2018-2019 respiratory season, with an anticipated cohort of 20 subjects and 20 controls. With regards to the murine studies, we have demonstrated that the lung microbiome of Sptlc2 +/− and Sptlc2 +/+ mice is similar at baseline (Figure 2) and remains similar following 1-day infection with rhinovirus. We do however, see a distinct change in the microbiome profile of the stool of Sptlc2 +/− mice following rhinovirus infection (Figure 3). Lung analysis at day 7 post infection is pending. DISCUSSION/SIGNIFICANCE OF IMPACT: These studies will lay the groundwork for detailing the functional role of the airway microbiome in bronchiolitis, with the objective of developing new modalities for disease treatment and prevention. In addition our murine studies allow us to view the microbiome in the context of sphingolipid deficiency, providing a potential mechanistic link to rhinovirus and ORMDL3 associated asthma.